Black Suburbanization: Causes and Consequences of a Transformation of American Cities - Bartik, Alexander W.; Mast, Evan (The Review of Economics and Statistics, 2026)
Abstract Since 1970, the share of Black individuals living in suburbs of large cities has risen from 16% to 36%. We first show that Black suburbanization has led to major changes in neighborhoods, accounting for the majority of recent increases in both the average Black individual’s neighborhood quality and income segregation within the Black population. We then use an accounting exercise to show that changes in relative suburban amenities and housing prices explain a large share of Black suburbanization, while regional reallocation, changing educational attainment, and gentrification of Black city neighborhoods play only minor roles.